Peran Sosialisasi Sekolah Demi Menciptakan Pembelajaran Kooperatif, Inovatif dan Selektif - Toyyibah, Niswatun; Ikrom, Bonafid; Abdullah, Iqbal; Maulana El-Yunusi, M. Yusron (Universitas Majalengka, 2024)
This research aims to determine socialization in schools using a cooperative learning model, using a qualitative research approach involving Tunas Buana Middle School Surabaya, that cooperative learning can involve students in learning collaboratively, exchanging ideas and being confident in expressing opinions. The results of this research were collected through interviews and observations, so it can be concluded that by using cooperative learning, students can develop thinking patterns and increase creativity in socializing, as well as having an impact on every lesson. So that students can develop their potential through innovative and selective learning.